2019
DOI: 10.1186/s12887-019-1466-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of family well-being on the quality of life of Indian children with thalassemia

Abstract: Background The association between chronic diseases and psychological problems is well established. As thalassemia is chronic blood disorder with burdensome treatment procedures, patients are likely to have psychological health problems. Many studies reported evidences regarding the quality of life. But, factors influencing the health-related quality of life with focus on psychological well-being were minimally studied. We aimed to find the factors contributing to the health-related quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
16
0
3
Order By: Relevance
“…A child with an educated mother had a better quality of life than a child with an uneducated mother. It is supported by research conducted by Thiyagarajan et al (2019), which found that parents' education was correlated with the quality of life of children with thalassemia.…”
Section: Parents' Educationmentioning
confidence: 83%
“…A child with an educated mother had a better quality of life than a child with an uneducated mother. It is supported by research conducted by Thiyagarajan et al (2019), which found that parents' education was correlated with the quality of life of children with thalassemia.…”
Section: Parents' Educationmentioning
confidence: 83%
“…Patients addressed that the disease therapy and its complications have affected their daily routine and sleeping patterns. Although Hydroxyurea has improved certain factors associated with the physical health of TDT patients still, it is debatable 17 . These complications hurt the physical and psychological health of Thalassemia children.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge about this disease, including the basic ones, the inheritance, the possibility, and the prevention, is a first key point to stop the increase of thalassemia case (Cao & Kan, 2013). This condition imposes not only physical burden but also an emotional and economic burden on the patient, their family, and the country (Colah et al, 2017;Riewpaiboon et al, 2010;Thiyagarajan et al, 2019). It is important to empower thalassemia patients and their families that have experience with this disease to convince the audience.…”
Section: Discussionmentioning
confidence: 99%